The Dynamic Interplay between Inflation, Economic Policy Uncertainty, and Economic Resilience in Emerging Markets: A Time-Varying Parameter Stochastic Volatility Vector Autoregression Analysis - Barguellil, Achouak (International Journal of Energy Economics and Policy, 2026)
This paper examines the complex and time-varying linkages between inflation, EPU, and economic resilience in emerging market economies. By applying a TVP-SV-VAR model on quarterly data from 2000 to 2024, we explore the dynamic interaction of these macroeconomic variables over time. Our results indicate that inflation and EPU exert a constant negative impact on economic resilience, with these impacts heterogeneous across different time periods and economic cycles. The analysis also shows that uncertainty and inflation demonstrate more pronounced negative effects during crisis times, implying that policy credibility and macroeconomic stability are accentuated when economies are under external shocks. The estimated stochastic volatility showed significant heteroskedasticity in all series, advocating the importance of considering time-varying volatility in macroeconomic modeling. Our results carry important implications for policymakers in emerging economies, highlighting the importance of credible monetary policy frameworks, transparent communication, and strong institutional arrangements necessary to build economic resilience.